The role of Brutonˈs tyrosine kinase in the development and BCR/TLR‐dependent activation of AM14 rheumatoid factor B cells. Issue 5 (1st November 2013) - Nündel, Kerstin; Busto, Patricia; Debatis, Michelle; Marshak‐Rothstein, Ann
Abstract : Brutonˈs tyrosine kinase signaling is not required for BCR/TLR‐dependent activation of autoreactive B cells. Abstract : The protein kinase Btk has been implicated in the development, differentiation, and activation of B cells through its role in the BCR and TLR signaling cascades. These receptors and in particular, the BCR and either TLR7 or TLR9 also play a critical role in the activation of autoreactive B cells by RNA‐ or DNA‐associated autoantigens. To explore the role of Btk in the development of autoreactive B cells, as well as their responses to nucleic acid‐associated autoantigens, we have now compared Btk‐sufficient and Btk‐deficient mice that express a prototypic RF BCR encoded by H‐ and L‐chain sdTgs. These B cells bind autologous IgG2a with low affinity and only proliferate in response to IgG2a ICs that incorporate DNA or RNA. We found that Btk‐sufficient RF + B cells mature into naïve FO B cells, all of which express the Tg BCR, despite circulating levels of IgG2a. By contrast, a significant proportion of Btk‐deficient RF + B cells acquires a MZ or MZ precursor phenotype. Remarkably, despite the complete inability of RF + Xid/y B cells to respond to F(ab′)2 anti‐IgM, RF + Xid/y B cells could respond well to autoantigen‐associated ICs. These data reveal unique features of the signaling cascades responsible for the activation of autoreactive B cells.